Ground Handling Operations Management: An Agent-Based Modelling Approach (Global Journal of Science Frontier Research, 2018)
This work addresses the resource allocation-routing problem in the aircraft Ground Handling (GH) context. This problem is classified as one of the challenges that most of the ground-handling operators face nowadays. It consists of allocating a number of resources including workers and vehicles to aircraft of different service requirements and specifications. The allocation deals with the assignment of m teams of n skilled workers to k special purpose vehicles to serve i aircraft on the air-side area, while the routing is to determine the optimal route used by a group of workers integrated with vehicles when serving one or more aircraft. Both the allocation and routing tasks are affected by a number of constraints including different aircraft types and sizes, different aircraft service times, and various GH operation details based on flight types. Therefore, the main aim of this research is to develop an autonomous system to deal with the allocation, planning, and scheduling of resources. The methodology followed involves a number of algorithms that act and interact with one another towards achieving the best allocation and routing process. The simulation results have shown a net decrease in the service time and an overall team utilisation of 92%.
Keywords: resource allocation; routing; aircraft; ground handling operations; autonomous system; algorithms; simulation